(3OjhGf CHj fhGSs - (3CHh fhGS , GdMSf Hf gGfjA Hf YHO GdGhd Hf UHGM GdMcej HGdhdGA, CHh fhGS,J (B198 (3g` s
(3ChdgG (B:s
(3jHJOF HGdaUd GdSGOS ef GdHGH GdJGSY (B((3bGajI GdOGd(B) s
(3BNQgG (B:s
(3GdHGH GdNGeS YTQ ef Led CNHGQg s
(3dYdg ef GdfSNI GdSGHbI Hg VHWs
(3hQO CjVkG JMJ Qbe (B2181 , 2191 , 475s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B240s
Keywords: (3GdCOHs